Providing Career Development Services to Veterans: Perceived Need, Acceptability, and Demand. (January 2021) - Stevenson, Brian J.; Gorman, Jay A.; Crossman, Donna M.; Mueller, Lisa
Providing career development services, through career counseling and assessment, is part of vocational rehabilitation programming. However, there is no applied evidence that such career development services are feasible or accepted among individuals with psychiatric disorders. We examined feasibility (acceptability, demand, and perceived need) of the Vocational Evaluation Center (VEC), one veterans affairs (VA) hospital's method of career development services for veterans with psychiatric disorders. Demographics, referral source, and service utilization were analyzed among 90 veterans referred to the VEC. Qualitative analysis identified patterns to veterans' reasons for seeking VEC services. Veterans referred to the VEC were predominately unemployed and disabled. Veterans tolerated the intervention well, with 16.7% dropping out. Reported needs for VEC services included (a) vocational uncertainty, (b) functional considerations in vocational planning, and (c) finding purpose. Veterans with psychiatric disorders want career development services. The VEC model appears feasible, well-tolerated, and aligned with consumers' needs.